2014
DOI: 10.2337/db14-0695
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Orexin Prevents Hepatic Insulin Resistance via Daily Bidirectional Regulation of Autonomic Nervous System in Mice

Abstract: Circadian rhythm is crucial for preventing hepatic insulin resistance, although the mechanism remains uncovered. Here we report that the wake-active hypothalamic orexin system plays a key role in this regulation. Wildtype mice showed that a daily rhythm in blood glucose levels peaked at the awake period; however, the glucose rhythm disappeared in orexin knockout mice despite normal feeding rhythm. Central administration of orexin A during nighttime awake period acutely elevated blood glucose levels but subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…Correspondingly, activation of orexin-expressing neurons in the LHA increases blood glucose levels through the stimulation of endogenous glucose production; notably, an intact autonomic outflow via the hepatic sympathetic innervation is essential for this effect [135]. A recent study has shown that knocking out orexin impairs daily rhythm in blood glucose levels [136]. In addition, treatment with an adrenergic antagonist or parasympathectomy suppresses the daynight oscillation of blood glucose levels induced by treatment with OX-A in normal and db/db mice [136].…”
Section: Autonomic Modulation Of Hepatic Glucose Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, activation of orexin-expressing neurons in the LHA increases blood glucose levels through the stimulation of endogenous glucose production; notably, an intact autonomic outflow via the hepatic sympathetic innervation is essential for this effect [135]. A recent study has shown that knocking out orexin impairs daily rhythm in blood glucose levels [136]. In addition, treatment with an adrenergic antagonist or parasympathectomy suppresses the daynight oscillation of blood glucose levels induced by treatment with OX-A in normal and db/db mice [136].…”
Section: Autonomic Modulation Of Hepatic Glucose Homeostasismentioning
confidence: 99%
“…A recent study has shown that knocking out orexin impairs daily rhythm in blood glucose levels [136]. In addition, treatment with an adrenergic antagonist or parasympathectomy suppresses the daynight oscillation of blood glucose levels induced by treatment with OX-A in normal and db/db mice [136]. In addition, the VMH has been shown to be involved in hepatic glucose homeostasis.…”
Section: Autonomic Modulation Of Hepatic Glucose Homeostasismentioning
confidence: 99%
“…Accordingly, elevated circulating glucose levels lead to reduced firing of orexin neurons, suggesting that orexins are part of a negative feedback loop, responding to energy status signals (Yamanaka et al, 2003). Recent evidence has also reported that central orexin can bidirectionally regulate hepatic gluconeogenesis, leading to generation of the daily blood glucose oscillation (Tsuneki et al, 2008;Tsuneki et al, 2013;Tsuneki et al, 2015). This mechanism, that is of relevance for circadian regulation of hepatic M A N U S C R I P T…”
Section: Orexin Neurons As Nutritional Sensorsmentioning
confidence: 99%
“…15 insulin sensitivity, is impaired by aging, when orexin deficiency enhanced endoplasmic reticulum (ER) stress in the liver leading to altered hepatic insulin signaling and abnormal gluconeogenic activity (Tsuneki et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Thus, although catecholamine projections to orexin neurons are necessary for orexin activation by glucoprivation, this does not preclude some independent orexin participation in other controls press.endocrine.org/journal/endo 2817 of food intake. A recent study, for example, reports that ablation of orexin neurons using ataxin-3 causes reduced food intake and activity during the dark phase of the circadian cycle, suggesting that an important role for orexin neurons is to coordinate activity state and food seeking based on circadian cues (46). The unusual nonmetabolic glucose-sensing properties of orexin neurons (29, 30) (discussed above) may contribute to their role in circadian control of activity and food intake or other functions of this diverse system of neurons.…”
mentioning
confidence: 99%